PENGARUH PENERAPAN MODEL PEMBELAJARAN BRAIN BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMP NEGERI 34 BANDAR LAMPUNG - Haryanto; Fitriana Rahmawati (Epsilon: Jurnal Pendidikan Matematika, 2019)
This study aims to determine the effect of Brain Based Learning on the ability to solve mathematical problems of eighth grade students of SMP Negeri 34 Bandar Lampung Academic Year 2017/2018. Learning is carried out on two classes, one class as an experimental class in learning using the Brain Based Learning model, and one class as a control class where in the learning process applying a conventional system. Where the experimental class was sampled in class VIII H, amounting to 35 students, and the control class was class VIII G, amounting to 33 students. Hypothesis testing uses the average two similarity test (ttes). From the results of testing the hypothesis obtained thit = 4.40. From tebel t distribution at a significant level of 5% it is known thit = t (1 - ½α) = 2.00 meaning thit> tdat is 4.40> 2.00 so it can be concluded that there is an influence on the application of the Brain Based Learning learning model to the problem solving ability mathematics students, especially in class VIII SMP Negeri 34 Bandar Lampung.